Misaligned Human Resource Allocation in Student-Led Religious Institutions: The Impact of Role Overload and a Proposed Capacity-Based Leadership Model - Zuyyina Ilmy Azizah (Visionaria: Journal of Educational Innovation Management, 2026)
This study is grounded in the issue of unequal task distribution within the management system of Islamic boarding schools involving university students who simultaneously serve as students, santri, and organizational administrators. These multiple responsibilities often lead to role overload, workload imbalance, and work inefficiency. This study aims to analyze the dynamics of role burden and formulate a capacity-based leadership model for optimizing task distribution. Using a qualitative case study approach at Nurul Jadid Islamic Boarding School, data were collected through observation, in-depth interviews, and documentation, then analyzed using the interactive model of Miles and Huberman. The findings indicate that task distribution remains administrative rather than capacity-based, resulting in unequal workloads, dependence on key individuals, and delays in organizational activities during intensive academic periods. In addition, organizational evaluation remains focused on program outcomes without monitoring workload balance among administrators. The novelty of this study lies in the development of a capacity-based leadership model that emphasizes the alignment between individual capacity, workload distribution, and organizational effectiveness within student-based Islamic boarding school organizations.